Análise do Estádio Municipal Professor Dario Rodrigues Leite, projeto de reforma e cobertura com utilização de técnicas ecológicas - Pagotto, Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This graduation work (T.G.) will analyze some features of the surroundings of the Estádio Municipal Professor Dario Rodrigues Leite as well as the interior of the building, as for the conservation state, the constructive techniques adopted in the implementation, the technology used Construction of the property, in addition to the observation of the existing structure and architecture. In this T.G., there is also a brief history of the main and most important Brazilian stadiums, which allowed to select what is more modern, interesting and efficient for civil construction materials, constructive techniques and architectural and structural models. Employees. A project of reform and coverage of the Municipal Stadium Professor Dario Rodrigues Leite was also elaborated from the studies conducted, using the Autodesk Revit software

Este Trabalho de Graduação (T.G.), irá analisar algumas características do entorno do Estádio Municipal Professor Dario Rodrigues Leite, assim como do interior do edifício, quanto ao estado de conservação, as técnicas construtivas adotadas na execução, a tecnologia utilizada na construção do imóvel, além da observação da estrutura e arquitetura existente. Neste T.G. consta também um breve histórico dos principais e mais importantes estádios brasileiros, o que permitiu selecionar o que há de mais moderno, interessante e eficiente quanto a materiais de construção civil, técnicas construtivas e modelos arquitetônicos e estruturais empregados. Também foi elaborado um projeto de reforma e de cobertura do Estádio Municipal Professor Dario Rodrigues Leite a partir dos estudos realizados, utilizando-se do software Autodesk Revit
Analysis of the Municipal Stadium Professor Dario Rodrigues Leite, project of reform and coverage with the use of ecological techniques
Keywords: Projeto arquitetonico; Materiais de construção; Industria de construção civil - Aspectos ambientais; Estádios; Building materials